Correct identification of limiting water data for water network synthesis - Foo, Dominic Chwan Yee; Manan, Zainuddin Abdul; El-Halwagi, Mahmoud M. (Springer Verlag, 2006)
Data extraction is one of the most critical steps in carrying out a process integration study for managing water usage and discharge. Correct identification of limiting water data during process integration for water minimisation has a significant impact on the water savings achievable for a given process. This paper presents the procedure and heuristics to extract the correct limiting water data from a process plant. In addition to limiting data on pollutant concentration, the paper discusses the optimal data extraction rules pertaining to flowrate of water demand and segregation of mixed streams. The paper also quantifies the consequences of inappropriate data extraction. Two case studies are used to illustrate the insights and consequences of data extraction in water minimisation problems.